Od humanizacji i strukturalizacji pracy do upełnomocnienia pracowników - aspekt etyczny - Bombała, Bronisław (Annales. Etyka w Życiu Gospodarczym, 2011)
The article analyses the main humanistic models in the theory of management. Seeking the answer to a question is an aim of analysisresearch: whether achievements of the humanistic current do the man good and help them with their development, or whether,on the contrary – have instrumental character and serve only increasing the effectiveness of the man as the employee? Discovering deepersources of the activity is crucial for fuller understanding the empowerment, which is developed in servant leadership.